2015
DOI: 10.1002/cncr.29504
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 clinical trial of sequential pralatrexate followed by a 48‐hour infusion of 5‐fluorouracil given every other week in adult patients with solid tumors

Abstract: BACKGROUND: Pralatrexate (PDX) is an inhibitor of dihydrofolate reductase that was rationally designed to improve cellular uptake and retention of the drug. Preclinical data have shown synergy with the sequential administration of a dihydrofolate reductase inhibitor followed 24 hours later by 5-fluorouracil (5-FU). METHODS: Twenty-seven patients were enrolled at 1 of 5 PDX dose levels from 75 to 185 mg/m 2 on day 1 followed 24 hours later by 5-FU at a dose of 3000 mg/m 2 /48 hours every 2 weeks with folic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Most genotype-directed dosing studies have tested differential dosing of irinotecan or other SN-38-related medications in patients carrying UGT1A1 variants [ 19 , 20 , 21 , 22 , 23 ]. Differential dosing for SN-38 was recommended in all studies.…”
Section: Genotype-directed Dosing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most genotype-directed dosing studies have tested differential dosing of irinotecan or other SN-38-related medications in patients carrying UGT1A1 variants [ 19 , 20 , 21 , 22 , 23 ]. Differential dosing for SN-38 was recommended in all studies.…”
Section: Genotype-directed Dosing Studiesmentioning
confidence: 99%
“…Others have evaluated variants in ABCB1 , CYP3A4 , CYP3A5 , UGT1A6 , UGT1A7 , and UGT1A9 ; however, only one study found UGT1A6 phenotype status was related to toxicity [ 37 ]. As stated previously, some Phase I studies have studied differential dosing in patients with different UGT1A1 allelic variants [ 19 , 20 , 21 , 22 , 23 ]. Eight studies provided no formal statistical analysis for an association between UGT1A1 genotypes and clinical data derived from phase I studies [ 19 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Frequently Tested Classes Of Anticancer Agentsmentioning
confidence: 99%